119 Size-dependent retention of stem cells following intracoronary injection. (16th May 2012) - Campbell, N G; Kaneko, M; Shintani, Y; Ikebe, C; Narita, T; Sawhney, V; Tano, N; Coppen, S R; Yashiro, K; Nourshargh, S; Mathur, A; Suzuki, K
Abstract : Background: Intracoronary (IC) injection of bone marrow mononuclear cells (BMMNCs) is a promising treatment for heart failure. However, therapeutic effects in clinical studies have been small and a principle reason may be related to poor donor cell engraftment. Very early donor cell retention may be an important factor to determine engraftment, but this process is largely unexplored. This study aimed to quantitatively characterise early donor cell retention after IC injection using an original experimental model. Methods: A modified ex-vivo Langendorff perfused rat heart model was developed (Abstract 119 figure 1 ). Known numbers of rat BMMNCs were injected into the aortic root of the perfused heart ("normal hearts"). The same cell numbers were injected into hearts subjected to 30 min global ischaemia and 30 min reperfusion ("I-R hearts"). 8×10 6 rat BM-derived mesenchymal stem cells (MSC), a larger cell type, were also injected into normal hearts. Coronary effluent was continuously collected and cell numbers in the effluent were counted. In this way, the number of cells retained could be quantitatively calculated. The cell size distribution and expression of relevant cell surface markers, both for BMMNC pre-injection and for BMMNC in the coronary effluent, were respectively measured with an automated cell counter and flow cytometry. Results: Median size was 7.0 and 11.0 μm for BMMNC and MSC respectively. Most leakage of donor cells into the coronary effluent occurred within 2 min. Calculated retention ratios for the three BMMNC numbers were similar; approximately 20% in normal hearts increasing to 30% after I-R (Abstract 119 table 1 ). The retention ratio for MSC injection was much higher. Surface markers of BMMNCs were unchanged between pre-injection and coronary effluent cells. Instead, it was found larger BMMNC were more frequently retained in normal hearts (Abstract 119 table 2 ). This retention pattern was magnified in I-R hearts: larger BMMNC were retained 6 times more efficiently than smaller cells. Histological studies using PKH-stained BMMNCs demonstrated that all BMMNC were observed within the lumen of small vessels and none were observed to have extravasated after 60 min (Abstract 119 figure 2 ). Coronary flow was not affected by injection of BMMNCs, whereas MSC injection led to a transient decrease of coronary flow. Conclusion: Our study using an original model showed retention rates of BMMNC in normal hearts were low regardless of the cell number injected, suggesting a critical limiting factor for the treatment's success. Retention rates were improved by I-R. Larger BMMNCs were retained with an increased efficiency. This information provides intriguing potential methods for increasing retention in future clinical studies, thereby enhancing the therapeutic effect.